Participatory heritage - Roued-Cunliffe, Henriette; Copeland, Andrea
This new book provides a wide range of international guidance and perspectives on the issues surrounding the preservation of local cultural heritage, ranging from formal cultural heritage institutions to individual community members in the associated processes of creation, organization, access, use and preservation. Participatory Heritage explores issues including, how to manage copyright, ownership, orphan works, open data access to heritage representations and artefacts, crowdsourcing, cultural heritage amateurs, information as a commodity or information as public domain, sustainable preservation, and attitudes towards openness. The book demonstrates that in order for personal and community-based documentation and artefacts to be preserved and included in social and collective histories, individuals and community groups need the technical and knowledge infrastructures of support that formal cultural institutions can provide. In other words, both groups need each other.